Pemphigoid diseases in patients with end-stage kidney diseases: pathogenesis and treatment - Yang, Liu-Yi-Yi; Wang, Yu-Lu; Zuo, Ya-Gang (Frontiers in Immunology, 2024)
Pemphigoid diseases constitute a group of autoimmune blistering disorders characterized by subepithelial blistering. The association between pemphigoid diseases and both end-stage kidney disease (ESKD) and its treatment is notable. However, there is limited evidence about the management of pemphigoid diseases in patients with ESKD. This systematic review compiled fifty-eight case reports and relevant studies, summarized the underlying mechanisms of pemphigoid diseases in patients with ESKD, and summarized the efficacy of various therapies. Removing triggers is the most effective strategy to improve treatment of pemphigoid diseases. Despite their suboptimal efficacy, corticosteroids remain the most commonly used agents in this patient population. Mycophenolate mofetil, tetracyclines, and biological agents such as rituximab are less used but with benefits. There are significant adverse effects associated with methotrexate treatment. Other treatment options, including dapsone, azathioprine, cyclosporine, intravenous immunoglobin, plasmapheresis, and Janus kinase inhibitors, may also be beneficial and require further investigation. Therefore, these findings may enable clinicians to optimize the therapeutic approach for these patients.